Assessment of microbial contamination of toothbrush head: An in vitro study - G N Karibasappa; L Nagesh; B K Sujatha (Wolters Kluwer Medknow Publications, 2011)
Background: The most common oral hygiene aid used to improve the oral health of an individual is toothbrush and it is often neglected to maintain in a proper aseptic condition, which could probably result in contamination by various micro-organisms. Aims: 1) To assess the microbial contamination of the hard deposit on the toothbrush head, between the bristle tufts, after 1 and 3 months of use. 2) To assess the microbial contamination of the hard deposit on the toothbrush head, between the bristle tufts, which were kept in the bathrooms with and without attached toilet. Setting and Design: An in vitro study. Materials and Methods: Twenty toothbrushes kept in the bathrooms with an attached toilet and 20 toothbrushes kept in the bathrooms without an attached toilet were collected from the participants, making it a total of 40. Among these 20 toothbrushes in each group, 10 were used for 1 month duration and 10 were used for 3 months duration. Results: Streptococcus mutans, Staphylococcus aureus, Pseudomonas, Lactobacillus, Klebsiella, Candida species were isolated in 1 month and 3 months used toothbrushes kept in the bathrooms without attached toilet. Escherichia coli was found in 3 months used toothbrushes kept in the bathrooms with attached toilet. Micro-organisms were found in isolated form in toothbrushes used for 1 month, whereas in toothbrushes used for 3 months they are found in clumps. Conclusion: Hard deposit on the toothbrush head between bristle tufts is a nidus for growth of micro-organisms, which not only affects the oral health but also affects the general health of an individual.